Dual Targeted Therapy: A Possible Option for the Management of Refractory Inflammatory Bowel Disease. (17th July 2020) - Privitera, Giuseppe; Onali, Sara; Pugliese, Daniela; Renna, Sara; Savarino, Edoardo; Viola, Anna; Ribaldone, Davide Giuseppe; Buda, Andrea; Bezzio, Cristina; Fiorino, Gionata; Fantini, Massimo Claudio; Scaldaferri, Franco; et al.
Abstract: Background and Aims: Dual targeted therapy [DTT] has been proposed as a novel therapeutic strategy for the management of complicated patients with inflammatory bowel diseases [IBD]. Our aim here was to investigate the safety and effectiveness of this approach in a real-life setting. Methods: We retrospectively extracted data from IBD patients receiving DTT in Italian IBD referral centres. Baseline characteristics, clinical activity of intestinal and extra-intestinal disease, and C-reactive protein levels were recorded. All adverse events were reported. Clinical effectiveness, biochemical remission and safety of DTT were investigated. Results: Sixteen patients were identified; indications for DTT were: 'active IBD' or 'active EIM' despite ongoing biological therapy. The most commonly used DTT were: vedolizumab + ustekinumab [three patients] and vedolizumab + adalimumab [three patients]. Clinical response of intestinal or extra-intestinal symptoms, according to the indication for DTT, was reported by all patients by the end of the induction. Four patients discontinued DTT during follow-up. Three patients experienced an adverse event; no serious adverse event was reported. Conclusions: DTT seems to be an effective and safe treatment and may represent an appealing therapeutic strategy for the management of complicated IBD patients.